Understanding Padangsidimpun City Community in Recognizing and Understanding Sharia Banking Products - Abdul Nasser Hasibuan; Nofinawati Nofinawati (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2021)
Abstract The population of Padangsidimpuan city is 89% Muslim who does not understand Islamic banking, and considers Islamic banking to be the same as conventional banks. The purpose of this paper is to determine the understanding of the people of Padangsidimpun city about Islamic banking products. The theory used is a general understanding, specific understanding, products about Islamic banking. The method used is PAR where the strategy used is a process of approach, research, learning and technical solutions to social problems that can be planned and implemented with the community. Results Public understanding of Islamic banking is only limited to 84 %. While the results of the specific understanding of the people of Padangsdimpuan city, namely the translation of Islamic products and banking, which is 12%, while the second level is an understanding of interpretation of 73%, and for the third level is the highest level, namely the understanding of extrapolation of the people of Padangsidimpuan city of 63%.